Strengthening the Branding of the BMT Mekarsari Mandiri Cooperative through Public Speaking and Creativity Training - Ahmad Maulana; Nurkardina Novalia; Aslamia Rosa; Umi Kalsum; Melisa Putri (Penerbit Goodwood, 2026)
Purpose: The purpose of this community service program is to enhance the branding of Koperasi Konsumen BMT Trans Mekarsari Mandiri by improving public speaking skills and creating engaging digital content for social media, thus increasing the cooperative’s visibility and market reach.Methodology: The methodology includes initial surveys and coordination with the cooperative’s management, followed by public speaking and content creation workshops. The implementation also involves ongoing mentoring and monitoring to ensure the effectiveness of the strategies introduced.Results: The program successfully improved participants' public speaking skills and ability to create creative content, such as short videos and digital posters. The cooperative’s branding efforts were strengthened, leading to better engagement on social media platforms like Instagram and Facebook. Participants showed increased confidence in promoting the cooperative, and there was noticeable improvement in the quality of content shared online. Conclusions: This community service program successfully empowered the cooperative’s management with essential skills in digital marketing and public communication, enabling Koperasi Konsumen BMT Trans Mekarsari Mandiri to enhance its branding and expand its reach. The skills acquired by the participants will contribute to the long-term sustainability and growth of the cooperative.Limitations: The program was limited by short duration and small participant scope.Contributions: This program contributes to community empowerment studies by integrating public speaking and digital content creation to improve cooperative branding and visibility.